Benefits and burdens of incorporation of companies in Nigeria (2008)
The present proposal by the Corporate Affairs Commission in Nigeria to de-register about four hundred thousand companies which have not been rendering their annual returns as stipulated by the provisions of the Companies and Allied Matters Act motivates the consideration of total attributes of corporate personality in this study. Nigeria has an estimated figure of about six hundred thousand registered companies, if about four hundred thousand Companies are deregistered; it remains two hundred thousand Companies. What could be the implication of such extinction? The essence of this study is not to discuss the merits and demerits of de- registration of Companies, but to sensitize the general public particularly the Corporate sector to the responsibilities of a registered company. It is the contention of this writer that lack of awareness of responsibility in a country dominated by high level of illiteracy could not be ruled out as one, if not the major reason, the four hundred thousand Companies failed to file their returns as at when due. In addition, research from the academics in the area of consequences of incorporation has been most of the time without a discourse on the responsibilities of a registered company. This study considers not only the procedure for registration of company but also the totality of the consequences of incorporation of companies dealing with its advantages and disadvantages et the same time. The study discusses how a company can be registered in Nigeria and the effect of such registration. On the same issue, it examines those who are competent to form a company and the choice of a valid name for the company. It argues that the consequences of the registration of Companies are not always positive but sometime negative.